Should the standard dimethyl sulfoxide concentration be reduced? Results of a European Group for Blood and Marrow Transplantation prospective noninterventional study on usage and side effects of dimethyl sulfoxide. Issue 10 (26th June 2014) - Morris, Curly; de Wreede, Liesbeth; Scholten, Marijke; Brand, Ronald; van Biezen, Anja; Sureda, Anna; Dickmeiss, Ebbe; Trneny, Marek; Apperley, Jane; Chiusolo, Patrizia; van Imhoff, Gustaaf W.; Lenhoff, Stig; et al.
<x xml:space="preserve">Abstract</x> Background Dimethyl sulfoxide (DMSO) is essential for the preservation of liquid nitrogen–frozen stem cells, but is associated with toxicity in the transplant recipient. Study Design and Methods In this prospective noninterventional study, we describe the use of DMSO in 64 European Blood and Marrow Transplant Group centers undertaking autologous transplantation on patients with myeloma and lymphoma and analyze side effects after return of DMSO‐preserved stem cells. Results While the majority of centers continue to use 10% DMSO, a significant proportion either use lower concentrations, mostly 5 or 7.5%, or wash cells before infusion (some for selected patients only). In contrast, the median dose of DMSO given (20 mL) was much less than the upper limit set by the same institutions (70 mL). In an accompanying statistical analysis of side effects noted after return of DMSO‐preserved stem cells, we show that patients in the highest quartile receiving DMSO (mL and mL/kg body weight) had significantly more side effects attributed to DMSO, although this effect was not observed if DMSO was calculated as mL/min. Dividing the myeloma and lymphoma patients each into two equal groups by age we were able to confirm this result in all but young myeloma patients in whom an inversion of the odds ratio was seen, possibly related to the higher dose of melphalan received by young myeloma patients. Conclusion We suggest better standardization of preservation method with reduced DMSO concentration and attention to the dose of DMSO received by patients could help reduce the toxicity and morbidity of the transplant procedure.